In vivo evidence that RBM5 is a tumour suppressor in the lung. Issue 1 (December 2017) - Jamsai, Duangporn; Watkins, D.; O'Connor, Anne; Merriner, D.; Gursoy, Selen; Bird, Anthony; Kumar, Beena; Miller, Alistair; Cole, Timothy; Jenkins, Brendan; O'Bryan, Moira
Abstract Cigarette smoking is undoubtedly a risk factor for lung cancer. Moreover, smokers with genetic mutations on chromosome 3p21.3, a region frequently deleted in cancer and notably in lung cancer, have a dramatically higher risk of aggressive lung cancer. The RNA binding motif 5 (RBM5) is one of the component genes in the 3p21.3 tumour suppressor region. Studies using human cancer specimens and cell lines suggest a role for RBM5 as a tumour suppressor. Here we demonstrate, for the first time, anin vivo role for RBM5 as a tumour suppressor in the mouse lung. We generatedRbm5 loss-of-function mice and exposed them to a tobacco carcinogen NNK. Upon exposure to NNK, Rbm5 loss-of-function mice developed lung cancer at similar rates to wild type mice. As tumourigenesis progressed, however, reducedRbm5 expression lead to significantly more aggressive lung cancer i.e. increased adenocarcinoma nodule numbers and tumour size. Our data providein vivo evidence that reduced RBM5 function, as occurs in a large number of patients, coupled with exposure to tobacco carcinogens is a risk factor for an aggressive lung cancer phenotype. These data suggest that RBM5 loss-of-function likely underpins at least part of the pro-tumourigenic consequences of 3p21.3 deletion in humans.